2013
DOI: 10.1094/mpmi-07-12-0172-fi
|View full text |Cite
|
Sign up to set email alerts
|

Aphid Protein Effectors Promote Aphid Colonization in a Plant Species-Specific Manner

Abstract: Microbial pathogens and pests produce effectors to modulate host processes. Aphids are phloem-feeding insects, which introduce effectors via saliva into plant cells. However, it is not known if aphid effectors have adapted to modulate processes in specific plant species. Myzus persicae is a polyphagous insect that colonizes Arabidopsis thaliana and Nicotiana benthamiana, while the pea aphid Acyrthosiphon pisum specializes on colonizing plant species of the family Fabaceae. We found that M. persicae reproductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
193
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(206 citation statements)
references
References 38 publications
10
193
2
1
Order By: Relevance
“…As a result, there is no capacity to increase plant susceptibility to the aphid by disrupting Ca 2+ signaling. The suppression of Arabidopsis defense by aphids is achieved via effector proteins (Bos et al, 2010;Hogenhout and Bos, 2011;Pitino and Hogenhout, 2013;Atamian et al, 2013;Elzinga et al, 2014;Naessens et al, 2015;Wang et al, 2015;Kettles and Kaloshian, 2016) that are injected into epidermal and mesophyll cells during feeding (Martín et al, 1997;Moreno et al, 2011;Mugford et al, 2016). These effectors may actively suppress the feeding site [Ca 2+ ] cyt elevations, as aphid saliva contains Ca 2+ binding proteins Carolan et al, 2009;Rao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, there is no capacity to increase plant susceptibility to the aphid by disrupting Ca 2+ signaling. The suppression of Arabidopsis defense by aphids is achieved via effector proteins (Bos et al, 2010;Hogenhout and Bos, 2011;Pitino and Hogenhout, 2013;Atamian et al, 2013;Elzinga et al, 2014;Naessens et al, 2015;Wang et al, 2015;Kettles and Kaloshian, 2016) that are injected into epidermal and mesophyll cells during feeding (Martín et al, 1997;Moreno et al, 2011;Mugford et al, 2016). These effectors may actively suppress the feeding site [Ca 2+ ] cyt elevations, as aphid saliva contains Ca 2+ binding proteins Carolan et al, 2009;Rao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aphid saliva contains Ca 2+ binding proteins Carolan et al, 2009;Rao et al, 2013), and application of saliva to legume phloemplugging proteins results in their contraction . Aphid saliva also contains effector molecules that suppress plant defense (Bos et al, 2010;Pitino and Hogenhout, 2013;Atamian et al, 2013;Naessens et al, 2015;Wang et al, 2015;Kettles and Kaloshian, 2016), as observed with microbial pathogens (Jones and Dangl, 2006;Galán et al, 2014) and chewing insects (Musser et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The plant-aphid interaction is complex and highly dynamic, subject to continual change (Mello and Silva-Filho 2002). Recently, studies have shown that aphids secrete effectors that modulate plant defence responses (Bos et al 2010;Atamian et al 2013;Pitino and Hogenhout 2013) pointing to parallels between plant-pathogen and plant-insect interactions (Jaouannet et al 2014). It has been suggested that two different processes are involved in the elicitation of plant defence.…”
mentioning
confidence: 99%
“…Plants have developed a sophisticated immune system against insect herbivory. Compared with our understanding of plant defensive responses against chewing insects, little is known about plant responses to phloem-feeding insects in the order Hemiptera (Van Oosten et al, 2008;Walling, 2008;Rodriguez-Medina et al, 2011;van Dam and Heil, 2011;Louis and Shah, 2013;Pitino and Hogenhout, 2013;Rao et al, 2013;VanDoorn et al, 2015). The detailed mechanisms of plant responses to this group of insects, such as aphids and whitefly (Bemisia tabaci Genn.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed mechanisms of plant responses to this group of insects, such as aphids and whitefly (Bemisia tabaci Genn. ), have only recently begun to be uncovered due to the small size and limited genetic and physiological information about these insects (Louis and Shah, 2013;Pitino and Hogenhout, 2013;VanDoorn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%